The Effect of Digital Literacy and Self Efficacy on the Job Readiness: A Case of Office Administration Education Students - Winarno Winarno; Patni Ninghardjanti; Anton Subarno; Muhammad Choerul Umam (Jurnal Pendidikan Progresif, 2024)
The Effect of Digital Literacy and Self Efficacy on the Job Readiness of FKIP UNS Office Administration Education Students. Objectives: This study aims to (1) determine the influence of digital literacy on the job readiness of FKIP UNS Office Administration Education students, class of 2021, (2) assess the impact of self-efficacy on the readiness to become teachers among FKIP UNS Office Administration Education students, class of 2020, and (3) evaluate the combined effect of digital literacy and self-efficacy on the job readiness of FKIP UNS Office Administration Education students, class of 2021. Methods: This quantitative study involved a saturated sampling technique, including all 84 students from the Office Administration Education Study Program, class of 2021. Data were collected through structured questionnaires and analyzed using linear regression with IBM SPSS software version 25. Findings: The results indicate that (1) digital literacy significantly influences job readiness, as evidenced by a t-value of 2.526, which is greater than the t-table value of 1.996, (2) self-efficacy also significantly impacts job readiness, with a t-value of 11.892, surpassing the t-table value of 1.996, and (3) digital literacy and self-efficacy jointly have a significant effect on job readiness, as demonstrated by an F-value of 148.801, exceeding the F-table value of 3.12.Conclusion: The study concludes that both digital literacy and self-efficacy positively and significantly contribute to the job readiness of students. These factors play a crucial role in preparing students for the workforce, both individually and collectively. Keywords: digital literacy, self-efficacy, job readiness.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202491